A variant selection mechanism in the deformed and recrystallized β matrix of a metastable β-titanium alloy. (3rd July 2018) - Panda, Subrata; Banerjee, Dipankar; Avadhani, Ganesh S.; Suwas, Satyam
ABSTRACT: The variant selection criteria during β to α phase transformations in a metastable β -titanium alloy (Ti-5553) in the presence of deformation are examined. Two distinct metallurgical states in the β matrix, heavily deformed and fully recrystallized, were obtained from a 90% cold-rolled alloy. The deformed and recrystallized samples were subjected to aging heat treatment for a short time to allow the precipitation of an intragranular α phase. Electron backscattered diffraction was used to assess the α crystallographic variant occurrence in the deformed as well as in the recrystallized β grains. A discrete pole figure analysis revealed that a limited number of variants were evolved in the deformed β grains while there was no variant selection in the recrystallized β matrix. The results suggest that activation of 112<111> β slip systems determines a strong variant selection in the plastically deformed β matrix.